Asuransi Syariah dalam Praktik (Studi Analisis Terhadap Shariah Compliance) - Desmadi Saharuddin (Faculty of Economic and Business, 2014)
The prohibition against gharar, gambling, and riba, is aimed to distance people from the act of taking property or the property of another by any wrongful means. In order to ensure those prohibited practices not happened in the company’s operations, syari’ah insurance company implements rules derived from the teachings of Islam. When conventional insurance can’t be separated from the elements of gharar, gambling, riba, riswah, and zhulm, the operation of syaria’ah insurance must be free from the prohibited practices, whether it is in the element of contract, product, investment, re-insurance, policy, marketing, or claims settlement. When conducting business with customers, syari’ah insurance must also be free from any transactions that contain elements of khidâ ', ghaban, tadlis, jahala, khiyânah, riswah, ihtikar. For syari’ah insurance to be free from those that are forbidden, the operation should not only focused on enforcing Islamic contract, products and systems alone, but also utilizes trusted human resources. Without the human resources that understand mu'amalah Shari'ah and Islamic law, the Islamic contracts will be easily diverted. Whatever the argument, there are chances that can create inconsistent practices with the basic foundation in Islamic financial institutions without exception on syari’ah insurance.DOI: 10.15408/ess.v4i3.2438